Hybrids in Literary Translation: Binary Translation Strategies in Howard Goldblatt’s English Translation of Mo Yan’s Frog - Jing Yang (Studia Metrica et Poetica, 2023)
Mo Yan’s Frog has been widely recognized and welcomed by readers since its publication. Apart from the Western readers’ love of Chinese culture, it also owes its popularity to the translator’s skillful handling of the translation. Specifically, this paper examines the translation strategies used in the English translation of Frog. The term hybrid translation is derived from Homi Bhabha’s hybrid theory, which advocates the mixing of different cultures in order to create a hybrid and fuzzy third space. This hybrid translation approach consists of mixing and integrating translation strategies, such as domestication and foreignization, literal translation and free translation, and finally forming a translation that reflects cultural hybridity. To demonstrate a cultural hybrid effect, translators must adopt a variety of approaches to the transformation of the text so that the target readers are able to fully understand its meaning and connotations.